The World Crisis : the Eastern Front. - Churchill, Winston S. (Winston Churchill World Crisis Collection., 2013)
The conclusion of the great statesman's epic five-volume history of World War I. The fifth and final volume of Winston Churchill's "remarkable" series The World Crisis (Jon Meacham) tells a gritty, true-to-life account of the Eastern Front'written by someone whose decisions had a profound impact on the success of war efforts both in the East and in the West. While the battle for modern civilization was being fought on the Western Front during World War I, an equally important war'with equally high stakes'was being fought on the Eastern Front, between Russia, Germany, and Germany's Austrian allies. It's rare that a historical account of World War I documents in as much detail the events of the Eastern Front as those of the West. Churchill's account was one of the first to do so, telling the story of an armed conflict that was shockingly dissimilar from its counterpart in the West. "Whether as a statesman or an author, Churchill was a giant; and The World Crisis towers over most other books about the Great War." 'David Fromkin, author of A Peace to End All Peace.